Effect of silicidation pretreatment with gaseous SiO on sinterability of TiC powders. (June 2016) - Istomin, P.; Istomina, E.; Nadutkin, A.; Grass, V.
Abstract: Silicidation pretreatment with gaseous SiO at 1350 °C for 30 min is employed for chemically modifying commercially available TiC powder. Phase composition and microstructural features of the pretreated powder are discussed. Densification behavior of the pretreated TiC powder during hot pressing is studied in comparison with that of non-pretreated one. Significantly improved densification behavior and sinterability of TiC powder after silicidation pretreatment are explained by the effect of Ti3 SiC2 acting as a solid lubricant. Nearly fully dense TiC-based ceramics having flexural strength of 370 MPa, fracture toughness of 5.6 MPa m ½, and microhardness of 24 GPa is obtained by hot pressing under conditions as mild as 1600 °C and 20 MPa. Highlights: Silicidation pretreatment with gaseous SiO enhances sinterability of TiC powder. Silicidation of TiC has good potential for use in fabrication of dense TiC ceramics. Nearly fully dense TiC ceramics is obtained by hot pressing at 1600 °C under 20 MPa. Ti3 SiC2 formed during silicidation of TiC powder promotes densification.